2015
DOI: 10.1038/srep12395
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcode reference library for Iberian butterflies enables a continental-scale preview of potential cryptic diversity

Abstract: How common are cryptic species - those overlooked because of their morphological similarity? Despite its wide-ranging implications for biology and conservation, the answer remains open to debate. Butterflies constitute the best-studied invertebrates, playing a similar role as birds do in providing models for vertebrate biology. An accurate assessment of cryptic diversity in this emblematic group requires meticulous case-by-case assessments, but a preview to highlight cases of particular interest will help to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(170 citation statements)
references
References 54 publications
9
160
0
1
Order By: Relevance
“…For the vast majority of cases, a priori defined butterfly species can also be delimited unambiguously based on DNA barcodes (Dincȃ et al 2011(Dincȃ et al , 2015Wilson et al 2013). Nevertheless, taxonomic uncertainties during the assembly of reference DNA barcode libraries challenges the use of DNA barcoding for routine species identification (i.e., the assignment of Linnaean species names to unknown specimens) (Collins and Cruickshank 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For the vast majority of cases, a priori defined butterfly species can also be delimited unambiguously based on DNA barcodes (Dincȃ et al 2011(Dincȃ et al , 2015Wilson et al 2013). Nevertheless, taxonomic uncertainties during the assembly of reference DNA barcode libraries challenges the use of DNA barcoding for routine species identification (i.e., the assignment of Linnaean species names to unknown specimens) (Collins and Cruickshank 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lepidoptera, the most intensively studied order, is represented by more than 100 000 BINs on BOLD. Work on this group has demonstrated the efficacy of DNA barcoding in identifying known species (Wilson et al 2013;Dinca et al 2015) and in revealing cryptic species complexes (Burns et al 2008;Huemer et al 2014a). It has also shown that there is very limited geographic variation in barcode sequences in populations of most species, so increased geographic scale does not reduce the success of species identification (Lukhtanov et al 2009;Huemer et al 2014b, Candek andKuntner 2015).…”
Section: Effectiveness Of Dna Barcodes For Arthropod Identificationmentioning
confidence: 99%
“…Bickford et al, 2007;Dincȃ et al, 2015;Vodȃ et al, 2015). As the traditional morphology-based species delimitation has its own limits, an integrative taxonomic approach is increasingly required.…”
Section: Introductionmentioning
confidence: 99%